Participation in Direct Spending Budget Against Local Original Revenue: Participation in Direct Spending Budget Against Local Original Revenue - Teniro, Alwin; Isma, Yuli Santri; Ashwad, Hajar (Universitas Ibn Khaldun Bogor, 2023)
The main problem analyzed in this study is how large and significant the contribution of the realization of the direct expenditure budget of the Public Works and Spatial Planning Office of Central Aceh Regency to Regional Original Revenue was during 2018-2022. The aim is to determine the progress of budget realization and Regional Original Revenue, as well as Direct Expenditure Budget Participation on Regional Original Revenue obtained by the agency. To solve the above problem, Seconds data was collected at the Public Works and Spatial Planning Office of Central Aceh Regency, then the data was analyzed with a determinant coefficient and tested with a t-test at a confidence level of 0.05. The results of the study found that the development of budget realization during 2018-2022 decreased by 19.93% per year as a result of a decrease in direct expenditure by 20.44% per year, thus causing a decrease in Regional Original Revenue by 0.05% per year. In addition, the realization of direct expenditure is positively correlated at 24.3% with a contribution of 5.90% but not significant. For this reason, it needs to be optimized through intensive levy levies to obtain greater direct budget realization in the future.